2013
DOI: 10.1186/1476-4598-12-162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-193a and sorafenib on hepatocellular carcinoma cells

Abstract: BackgroundHepatocellular carcinoma (HCC) is a challenging malignancy of global importance, it is the third most common cause of cancer-related mortality worldwide. In the last years the multikinase inhibitor sorafenib has been used for advanced HCC, but some patients do not benefit from this therapy; thus, novel therapeutic options based on molecular approaches are urgently needed. microRNAs are short non coding RNAs involved in several physiological and pathological conditions including HCC and increasing evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 32 publications
(36 reference statements)
3
88
1
Order By: Relevance
“…However, treatment outcomes are poor due to unfavorable pharmacokinetics, low tumor accumulation and high rates of sorafenib resistance in HCC patients (5). Evidence has shown that, some miRNAs increased sorafenib sensitivity to HCC cells (13,(38)(39)(40). In addition, inhibition of the activation of Akt may be a valid approach to treating human malignancies and overcoming the resistance of cancer cells to chemotherapy (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment outcomes are poor due to unfavorable pharmacokinetics, low tumor accumulation and high rates of sorafenib resistance in HCC patients (5). Evidence has shown that, some miRNAs increased sorafenib sensitivity to HCC cells (13,(38)(39)(40). In addition, inhibition of the activation of Akt may be a valid approach to treating human malignancies and overcoming the resistance of cancer cells to chemotherapy (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that miR-193a-3p is associated with apoptosis and proliferation in cancer cells (25,26). We examined two markers of apoptosis, PARP and caspase-3, to investigate the alteration in apoptosis after the introduction of miR-193a-3p in DSS-induced colitis.…”
Section: Mir-193a-3p Reduces the Intestinal Inflammatory Response In mentioning
confidence: 99%
“…Recent studies have revealed that miR-193a-3p is associated with apoptosis and proliferation of human malignancies, such as hepatocellular carcinoma and glioblastoma. Kwon et al (26) presented a novel miR-193a-3p-dependent mechanism for regulating Mcl-1 expression and inducing apoptosis, whereas Salvi et al (25) found that miR-193a-3p was dysregulated in tumor tissues from patients, and transfection of miR-193a-3p decreased proliferation and increased apoptosis in HCC cell lines. We also analyzed PARP cleavage and caspase-3 activation to investigate the alteration in apoptosis after miR-193a-3p was introduced in DSS-induced colitis.…”
Section: Mir-193a-3p Reduces Intestinal Inflammationmentioning
confidence: 99%
“…Dysregulation of miR193a-3p has been reported in various types of cancer, such as NSCLC (29), prostate cancer (30), breast cancer (31), head and neck squamous cell carcinoma (32), colorectal cancer (33), myeloid leukemia (34), and Wilms tumor (35). The carcinogenic impact of miR-193a-3p has been attributed to its repression of c-Kit (34) and the PTEN/PI3K signaling pathway in acute myeloid leukemia (34); of KRAS and PLAU in colon cancer (36); of PLAU (37) and EGFR-driven cell cycle network proteins (38) in breast cancer; of ARHGAP19, CCND1, ERBB4, KRAS, and Mcl-1 in epithelial ovarian cancer (39); of PLAU in hepatocellular carcinoma (40); and of Mcl-1 in NSCLC (41). Thus, miR-193a-3p functions as a tumor suppressor in human cancers.…”
mentioning
confidence: 99%